Preparation method and application of core-shell structure nano zinc oxide blocking agent with rigid inside and soft outside for marine drilling fluid
By using nano zinc oxide sealant in deep water drilling fluid, the problems of micro-nano pore sealing and hydrate generation in deep water drilling fluid are solved, and the stability and safety of the well wall are improved.
Patent Information
- Application Number
- CN202411914748.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
During deep-water drilling, the existing technology is difficult to effectively block micro-nano-scale pores in shale formations, resulting in unstable well walls and unsuitable for deep-water high-pressure and low-temperature environments, which has the problem of hydrate generation.
Nano-zinc oxide sealing agent with rigid inner and flexible core-shell structure is used to polymerize acrylamide and 2-acrylamide-2-methylpropanesulfonic acid and graft it on the surface of modified nano-zinc oxide to form a core-shell structure zinc oxide sealing agent with rigid inner and flexible outer micro-shaped core-shell structure to seal the micro-nano-scale pores in the formation and inhibit the formation of hydrates.
Effectively seal the micro-nano-scale pores in deep water formations, prevent drilling fluid filtrate from invading, maintain the stability of the well wall, inhibit the generation of hydrates, and improve the safety and efficiency of the deep water drilling process.
Smart Images

Figure BDA0005206571680000071 
Figure BDA0005206571680000081 
Figure BDA0005206571680000082
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a nano zinc oxide plugging agent with a hard-inside-soft-outside core-shell structure for marine drilling fluid, and belongs to the field of deepwater oil and gas development. Background Art
[0002] In recent years, most of the world's major oil and gas resource discoveries (about 50%) have come from deep-sea areas. The Gulf of Mexico, Brazilian waters, West Africa and the South China Sea are the main hotspots for deep-water oil and gas. my country's South China Sea is rich in oil and gas resources, accounting for one-third of the total, of which 70% are hidden in the deep sea. Marine deep-water oil and gas exploration and development has become the core concern and scientific research frontier of the oil industry.
[0003] In deepwater formation drilling, the requirements for drilling fluid treatment agents are getting higher and higher. This is mainly because the deepwater formation environment is complex, and the pressure, temperature and other conditions of the formation have a greater impact on the performance of the drilling fluid. Therefore, the drilling fluid needs to have higher stability to ensure drilling efficiency and safety. In drilling operations, it is crucial to maintain the stability of the wellbore. The main reason for the instability of the wellbore is the infiltration of drilling fluid filtrate, which will cause the formation to absorb water and swell, reduce strength, and eventually may cause the wellbore to collapse and cause a well collapse accident. This situation is particularly common in swellable formations such as shale. In order to prevent filtration intrusion and ensure the stability of the wellbore, effective strategies need to be adopted to plug the pores in the shale formation. The low permeability, micropores and microcracks of shale formations make the pore size mainly in the range of 5-30nm, which puts higher requirements on the selection of plugging materials. It is necessary to select plugging materials with suitable particle sizes that can enter the micropores and microcracks of shale, effectively plug the pores, prevent further intrusion of drilling fluid filtrate, and maintain the stability of the wellbore.
[0004] In recent years, the application of nanotechnology in the field of drilling has led to the rapid development of the oil exploration industry. Researchers have conducted in-depth research on the use of nanomaterials in drilling fluids and found that these materials can effectively seal the tiny pores of fine-fracture formations such as mudstone, significantly reduce the permeability and pressure transmission of shale, thereby enhancing the bearing capacity of the formation and improving the stability of the wellbore. The application of nanoparticles in drilling fluids has the advantages of reducing formation damage, enhancing rheology, and maintaining wellbore stability. However, since the silanol groups on the surface of nanoparticles are easy to polymerize, it is difficult to disperse in the drilling fluid, so that the ideal nanosize effect cannot be exerted, which reduces the overall performance of the drilling fluid. In order to solve the problem of easy aggregation of nanoparticles, researchers have improved their dispersibility in drilling fluids by chemically modifying them. The experimental results show that the use of these chemically modified nanoparticles as drilling fluid additives can significantly reduce the filtration loss and play a positive role in the protection of oil and gas reservoirs. Therefore, in-depth research on the research and development of plugging agents for deepwater drilling fluids and their mechanism of action has important practical application value for the oil exploration industry.
[0005] In deepwater environments, the formation is undercompacted, and there are large sections of soft mud shale with many nanopores. At the same time, the secondary generation of hydrates is very likely to occur in deepwater, high-pressure, and low-temperature environments. In order to ensure safe and efficient drilling operations, a large amount of hydrate thermodynamic inhibitors need to be added, which is costly and causes serious environmental pollution. At the same time, existing chemically modified nanoparticles are not suitable for deepwater, high-pressure, and low-temperature environments, and their use is limited.
[0006] At present, there is still no report on targeted products in domestic and foreign public literature. Therefore, it is particularly important to develop a nano plugging agent for deepwater drilling fluid that can plug nanopores and inhibit hydrate formation. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a preparation method and application of a nano zinc oxide plugging agent with a hard-inside-soft-outside core-shell structure for marine drilling fluid.
[0008] The nano zinc oxide plugging agent with a rigid inner and flexible outer core-shell structure of the present invention can effectively plug the micro-nano pores in deepwater formations, prevent the drilling fluid filtrate from further invading the formation, and can effectively inhibit the formation of hydrates, which is beneficial to protecting the stability of the well wall during deepwater drilling, reducing reservoir hydration dispersion, and improving the safety of the deepwater drilling process.
[0009] The technical solution of the present invention is as follows:
[0010] A method for preparing a nano zinc oxide plugging agent with a hard inner and soft outer core-shell structure for marine drilling fluid comprises the following steps:
[0011] The acrylamide aqueous solution, 2-acrylamide-2-methylpropanesulfonic acid solution and KH570 modified nano zinc oxide solution are uniformly mixed; under a protective atmosphere and stirring conditions, an initiator aqueous solution is added dropwise; the mixture is stirred and reacted under a protective atmosphere, and then washed, dried and crushed to obtain a modified nano zinc oxide core-shell structure plugging agent for marine drilling fluid.
[0012] Preferably according to the present invention, the mass concentration of the acrylamide aqueous solution is 6-15%.
[0013] Preferably according to the present invention, the mass concentration of the 2-acrylamide-2-methylpropanesulfonic acid solution is 20-26%, and the solvent is water.
[0014] Preferably according to the present invention, the mass concentration of the KH570 modified nano zinc oxide solution is 15-25%, and the solvent is water.
[0015] Preferably according to the present invention, the molar ratio of acrylamide to 2-acrylamido-2-methylpropanesulfonic acid is (1-3):1.
[0016] Most preferably, the molar ratio of acrylamide to 2-acrylamido-2-methylpropanesulfonic acid is 1:1.
[0017] Preferably according to the present invention, the molar ratio of acrylamide to KH570 modified nano zinc oxide is 1:(1-6).
[0018] Further preferably, the molar ratio of acrylamide to KH570 modified nano zinc oxide is 1:(2-4).
[0019] Preferably, according to the present invention, the mixing is carried out under stirring conditions, the stirring rate is 200-300 rpm, the stirring time is 10-20 minutes, and the mixing temperature is 15-25°C;
[0020] According to the present invention, preferably, the protective atmosphere is nitrogen.
[0021] Preferably according to the present invention, the mass concentration of the initiator aqueous solution is 0.9%-1.5%; and the initiator is ammonium persulfate.
[0022] Preferably according to the present invention, the mass of the initiator is 0.5%-1% of the total mass of acrylamide, dimethyldiallylammonium chloride and KH570 nano zinc oxide.
[0023] Further preferably, the mass of the initiator is 0.5%-0.8% of the total mass of acrylamide, dimethyldiallylammonium chloride and KH570 nano zinc oxide.
[0024] According to the preferred embodiment of the present invention, the dripping rate of the initiator aqueous solution is one drop every 2-4 seconds.
[0025] Preferably according to the present invention, after the initiator is added dropwise, the stirring reaction temperature is 65-85° C., the stirring speed is 20-35 rpm, and the stirring reaction time is 6 hours.
[0026] According to the preferred embodiment of the present invention, washing is performed using ethanol; and the drying temperature is 65-85°C.
[0027] The invention adopts acrylamide and 2-acrylamide-2-methylpropane sulfonic acid to polymerize and graft on the surface of modified nano zinc oxide to form a core-shell structure zinc oxide plugging agent with a microscopic morphology of hard inside and soft outside, with modified nano zinc oxide as the core and a polymer shell layer coated on the outside.
[0028] A nano zinc oxide plugging agent with a hard-inside-soft-outside core-shell structure for marine drilling fluid is prepared by the method.
[0029] The above-mentioned nano zinc oxide plugging agent with a rigid inner and flexible outer core-shell structure for marine drilling fluid is used as a plugging agent in deep-water reservoir drilling to plug micro-nano pores in the formation and inhibit the formation of natural gas hydrates. The addition amount is 1-5g / 300-600mL.
[0030] The technical features and beneficial effects of the present invention are as follows:
[0031] 1. The present invention uses acrylamide and 2-acrylamide-2-methylpropane sulfonic acid to polymerize and graft on the surface of modified nano zinc oxide to form a core-shell structure zinc oxide plugging agent with a microscopic morphology of hard inside and soft outside; with the help of the rigid plugging of nano materials and the flexible plugging of deformation filling of high molecular polymers, the soft and hard are combined to effectively plug the micro-nano pores of mud shale, thereby maintaining the stability of the well wall, and effectively inhibiting the secondary generation of hydrates, improving the safety and efficiency of deep-water drilling, the preparation method is simple, the raw materials are cheap and easy to obtain, and the process is efficient and environmentally friendly; and the process has good compatibility with the drilling fluid.
[0032] 2. The molecular chain of acrylamide can flexibly fill and adapt to the different shapes and sizes of microcracks or pores, providing flexibility to enhance the plugging effect. 2-Acrylamide-2-methylpropanesulfonic acid (AMPS) can enhance the heat and salt resistance of the polymer. At the same time, AMPS contains sulfonic acid groups and hydroxyl groups, which increase the thermal stability of the polymer. Stronger bonding CS and CN bonds also improve the heat resistance; the cations of dimethyldiallylammonium chloride (DMDAAC) will be adsorbed on the clay surface through electrostatic action, and a part of them will enter the interlayer to replace the interlayer cations, thereby expelling the interlayer water molecules. The positive charge provided by DMDAAC can form a strong charge adsorption with the negatively charged clay minerals in the mudstone, enhancing the plugging and inhibition effect of the polymer; the specific ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and modified nano zinc oxide in the present invention makes the obtained plugging agent have a complete shell layer and the polymer shell layer has better flexibility, forming a core-shell structure zinc oxide plugging agent with inner rigidity and outer softness, which has a stronger micron-level plugging ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the infrared spectrum of the nano plugging agent prepared in Example 1.
[0034] Figure 2 This is the thermogravimetric analysis diagram of the nano plugging agent prepared in Example 1.
[0035] Figure 3 This is a particle size analysis diagram of the nano plugging agent prepared in Example 1. DETAILED DESCRIPTION
[0036] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.
[0037] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents, materials and equipment described are all commercially available unless otherwise specified.
[0038] Example 1
[0039] The preparation method of the inner-rigid and outer-flexible core-shell structure nano zinc oxide plugging agent for marine drilling fluid comprises the following steps:
[0040] (1) 4.6 g (0.065 mol) of acrylamide and 50 g of pure water were uniformly mixed at 25° C. and stirred for 15 minutes at a stirring rate of 200 r / min to obtain an acrylamide aqueous solution;
[0041] (2) adding 13.40 g (0.065 mol) of 2-acrylamide-2-methylpropanesulfonic acid to the aqueous acrylamide solution obtained in step (1), stirring the mixture for 15 minutes at a stirring rate of 200 r / min and a temperature of 25° C. to obtain a mixed solution of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid;
[0042] (3) 12 g (0.147 mol) of KH570 modified nano zinc oxide was uniformly mixed with 60 g of pure water at 25° C., and stirred for 15 minutes at a stirring rate of 200 r / min to obtain a KH570 modified nano zinc oxide aqueous solution;
[0043] (4) Add the mixed solution of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid and the KH570 modified nano zinc oxide aqueous solution into a 250 mL three-necked flask and mix them evenly. Place the flask in a constant temperature water bath and continue to introduce nitrogen for 15 minutes at a temperature of 65° C. and a rotation speed of 30 rpm to expel the air in the flask while continuing to stir.
[0044] (5) Weigh 0.09g of ammonium persulfate initiator and dissolve it in 10mL of pure water to obtain 10mL of ammonium persulfate initiator aqueous solution. Under stirring conditions and nitrogen protection, add the initiator aqueous solution to the three-necked flask at a rate of 3 seconds per drop; after the addition is completed, continue to react for 6 hours at a stirring rate of 30r / min, a temperature of 65°C and nitrogen conditions; after the reaction is completed, wash with anhydrous ethanol, dry in an electric constant temperature blast drying oven at 60°C for 24h, and crush to obtain a core-shell structured nano zinc oxide plugging agent with a rigid inner core and a soft outer core.
[0045] The IRTracer-100 infrared spectrometer was used to perform infrared testing on the nano zinc oxide plugging agent with a rigid inner and flexible outer core-shell structure prepared in this embodiment using a KBr tabletting method. Figure 1 .
[0046] from Figure 1 It can be seen that 3433cm -1 The stretching vibration peak of amino group -NH2 appears near 1602cm -1 The absorption peak of carbonyl -C=O in the amide group appears nearby, 1363 cm -1 It is the characteristic peak of carbon-carbon double bond -C=C, 1190cm -1 It is the antisymmetric stretching vibration peak of the sulfonic acid group -SO3H, 1043cm -1 It is the symmetrical stretching vibration peak of the sulfonic acid group. The infrared spectrum analysis results show that the product contains the characteristic functional groups of various monomers in the molecular structure design, indicating that each monomer participates in the polymerization reaction and the target product is successfully synthesized.
[0047] Thermogravimetric / differential thermal analysis was performed on the hard-inside-soft-outside core-shell structure nano zinc oxide plugging agent prepared in this embodiment using a thermogravimetric analyzer TGA. Figure 2 As shown, the first stage is 40-310℃, and the product slowly loses weight by 9.8%. Since the copolymer contains a large number of hydrophilic groups such as amide groups, the weight loss mainly comes from water between and inside the molecules. The second stage is 310-490℃, the product begins to decompose, the carbon-carbon main chain begins to break, and the functional groups on the KH570 modified nano zinc oxide also degrade, with a weight loss of 33.2%. The third stage is 490-800℃, the polymer chain continues to carbonize and break, and at the final temperature of 800℃, the product still retains 37% of its mass. In summary, it can be seen that the functional groups contained in the nano plugging agent for deepwater drilling fluid have good thermal stability.
[0048] The nanometer particle size potentiometer was used to analyze the particle size of the nano zinc oxide plugging agent with a hard inner and soft outer core-shell structure prepared in this embodiment. Figure 3 As shown, the particle size distribution of the nanoparticles is relatively concentrated, and the curve is peak-shaped, the distribution range is between 200-300 nm, and the average particle size is 240 nm.
[0049] Example 2
[0050] The preparation method of the inner-rigid and outer-flexible core-shell structure nano zinc oxide plugging agent for marine drilling fluid comprises the following steps:
[0051] (1) 6.11 g (0.086 mol) of acrylamide and 50 g of pure water were uniformly mixed at 25° C. and stirred for 15 minutes at a stirring rate of 200 r / min to obtain an acrylamide aqueous solution.
[0052] (2) 11.89 g (0.057 mol) of 2-acrylamide-2-methylpropanesulfonic acid was added to the aqueous acrylamide solution obtained in step (1), and the mixture was stirred for 15 minutes at a stirring rate of 200 r / min and a temperature of 25° C. to obtain a mixed solution of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid.
[0053] (3) 12 g (0.147 mol) of KH570 modified nano zinc oxide was uniformly mixed with 60 g of pure water at 25° C. and stirred for 15 minutes at a stirring rate of 200 r / min to obtain a KH570 modified nano zinc oxide aqueous solution.
[0054] (4) Add the mixed solution of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid and the KH570 modified nano zinc oxide aqueous solution into a 250 mL three-necked flask and mix them evenly. Place the flask in a constant temperature water bath at 85°C and 30 rpm, and continue to introduce nitrogen for 15 minutes to expel the air in the flask while continuing to stir.
[0055] (5) Weigh 0.12g of ammonium persulfate initiator and dissolve it in 10mL of pure water to obtain 10mL of ammonium persulfate initiator aqueous solution. Under stirring and nitrogen protection, add the initiator aqueous solution to the three-necked flask at a rate of 3 seconds per drop; after the addition is completed, continue to react for 6 hours at a stirring rate of 30r / min, a temperature of 85°C and nitrogen conditions; after the reaction is completed, wash with anhydrous ethanol, dry in an electric constant temperature blast drying oven at 60°C for 24h, and crush to obtain a core-shell structured nano zinc oxide plugging agent with a rigid inner core and a soft outer core.
[0056] Example 3
[0057] The preparation method of the inner-rigid and outer-flexible core-shell structure nano zinc oxide plugging agent for marine drilling fluid comprises the following steps:
[0058] (1) 7.32 g (0.103 mol) of acrylamide and 50 g of pure water were uniformly mixed at 25° C. and stirred for 15 minutes at a stirring rate of 200 r / min to obtain an acrylamide aqueous solution.
[0059] (2) 10.68 g (0.052 mol) of 2-acrylamide-2-methylpropanesulfonic acid was added to the aqueous acrylamide solution obtained in step (1), and the mixture was stirred for 15 minutes at a stirring rate of 200 r / min and a temperature of 25° C. to obtain a mixed solution of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid.
[0060] (3) 12 g (0.147 mol) of KH570 modified nano zinc oxide was uniformly mixed with 60 g of pure water at 25° C. and stirred for 15 minutes at a stirring rate of 200 r / min to obtain a KH570 modified nano zinc oxide aqueous solution.
[0061] (4) Add the mixed solution of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid and the KH570 modified nano zinc oxide aqueous solution into a 250 mL three-necked flask and mix them evenly. Place the flask in a constant temperature water bath at 75°C and 30 rpm, and continue to introduce nitrogen for 15 minutes to expel the air in the flask while continuing to stir.
[0062] (5) Weigh 0.12g of ammonium persulfate initiator and dissolve it in 10mL of pure water to obtain 10mL of ammonium persulfate initiator aqueous solution. Under stirring conditions and under nitrogen protection, add the initiator aqueous solution to the three-necked flask at a rate of 3 seconds per drop; after the addition is completed, continue to react for 6 hours at a stirring rate of 30r / min, a temperature of 75°C and nitrogen conditions; after the reaction is completed, wash with anhydrous ethanol, dry in an electric constant temperature blast drying oven at 60°C for 24h, and crush to obtain a core-shell structured nano zinc oxide plugging agent with a rigid inner core and a soft outer core.
[0063] Comparative Example 1
[0064] A method for preparing a nano plugging agent is carried out according to Example 1, except that:
[0065] The reaction temperature was 85°C, and the other steps and conditions were the same as those in Example 1.
[0066] Comparative Example 2
[0067] A method for preparing a nano plugging agent is carried out according to Example 1, except that:
[0068] The amount of acrylamide used was 6.11 g (0.086 mol), the amount of 2-acrylamido-2-methylpropanesulfonic acid used was 11.89 g (0.057 mol), the amount of ammonium persulfate used was 0.15 g, and the other steps and conditions were the same as those in Example 1.
[0069] Comparative Example 3
[0070] A method for preparing a nano plugging agent is carried out according to Example 1, except that:
[0071] The amount of acrylamide used was 7.32 g (0.103 mol), the amount of 2-acrylamido-2-methylpropanesulfonic acid used was 10.68 g (0.052 mol), the amount of ammonium persulfate used was 0.15 g, the reaction temperature was 85° C., and the other steps and conditions were the same as in Example 1.
[0072] Experimental example
[0073] 1. Rheological filtration test:
[0074] Preparation of base slurry: 400 mL of distilled water, 0.6 g of sodium carbonate, and 20 g of bentonite for drilling fluid test slurry are stirred at high speed on a high-speed stirrer for 20 minutes, and then sealed and cured at 25℃±1℃ for 24 hours.
[0075] Sample preparation for the embodiments and comparative examples: 6 portions of 400 mL of the base slurry were taken, 2 g of the sample of the embodiments or comparative examples were added respectively, and the mixture was stirred at 7000 r / min for 20 min.
[0076] Aging of samples of the embodiments and comparative examples: the sample slurry was placed in a high-temperature roller heating furnace and aged at 180° C. for 16 h. After the aging was completed, the slurry was taken out and cooled, and stirred at 7000 r / min for 20 min.
[0077] With reference to the national standard "GB / T 29170-2012 Laboratory Test of Drilling Fluids in the Petroleum and Natural Gas Industry", the rheological parameters of the base slurry of the embodiment or comparative example sample, as well as the filtration loss at room temperature and pressure and the filtration loss at high temperature and high pressure after aging were measured. The experimental results are shown in Table 1.
[0078] Table 1 Rheological filtration test of the base slurry of the examples and comparative examples
[0079]
[0080]
[0081] It can be seen from Table 1 that the apparent viscosity (AV) and plastic viscosity (PV) of the base slurry added to the example or comparative example before aging increased, and the filtration loss at room temperature and pressure was significantly reduced; after aging at 180°C, the apparent viscosity (AV) and plastic viscosity (PV) of the base slurry added to the example or comparative example remained basically unchanged, and the filtration loss at high temperature and high pressure was significantly reduced. Among them, the FL of the base slurry added to the sample of Example 1 before and after aging API 11.2mL and 58mL respectively. By comparing Example 1 with Examples 2, 3 and Comparative Examples 2, 3, it can be found that with the increase in the amount of 2-acrylamide-2-methylpropane sulfonic acid, the increase in the sulfonic acid group can increase the rigidity of the polymer chain, so that it can form a more effective plugging structure; the sulfonic acid group has good high temperature resistance, which can further improve the plugging performance of the product in a high temperature environment. By comparing Example 1 with Comparative Example 1, it can be found that the present invention can further improve the plugging ability of the product and reduce the filtration loss by changing the appropriate reaction temperature.
[0082] 2. Hydrate formation inhibition evaluation experiment:
[0083] Open the gas pipeline and methane cylinder, use the gas booster to increase the pressure to 20MPa, prepare 0.5% nano plugging agent aqueous solution and pure water and place them in the reactor, start the vacuum pump, and evacuate for 15 minutes to reduce the pressure in the reactor to -0.09MPa. Inject 14MPa of pressure into the reactor, start temperature control and stirring, and ensure that the pressure in the reactor remains at 14MPa when the temperature starts to drop uniformly.
[0084] The data acquisition system is used to record the data including liquid temperature, gas temperature, pressure, stirring torque, etc. in real time. The experimental results are shown in Table 2.
[0085] Table 2 Hydrate formation inhibition test
[0086]
[0087] As can be seen from Table 2, compared with pure water, adding 0.5% of Example 1 can extend the time for large-scale hydrate formation from 3.80 h to 5.95 h, and reduce the large-scale formation temperature from 11.10° C. to 4.61° C., indicating that Example 1 has good hydrate formation inhibition performance.
[0088] 3. Microporous membrane filtration loss experiment:
[0089] A microporous filter membrane with nano-scale pores was used to simulate the pores of deep-water formations, and the filtration loss of samples was measured at room temperature and pressure using microporous filter membranes with different pore sizes. The results are shown in Table 3.
[0090] Table 3 Microporous membrane filtration test
[0091]
[0092] It can be seen from Table 3 that, compared with pure water, Example 1 can effectively block nano-scale pores of different sizes, thereby significantly reducing the filtration loss of the microporous membrane, indicating that Example 1 has good blocking ability.
[0093] 4. Medium pressure sand bed plugging experiment:
[0094] The 160-180 mesh sand was used to simulate the micro-nano pores in different environments in the formation, and the plugging performance of the samples was tested. The results are shown in Table 4.
[0095] Table 4 Medium pressure sand bed plugging experiment
[0096]
[0097] It can be seen from Table 4 that all the base slurry after hot rolling is lost, while the penetration depth of the base slurry after hot rolling + 0.5% Example 1 in the sand bed is 5.1 cm, indicating that Example 1 has a good plugging ability.
[0098] Comparative Example 4
[0099] A method for preparing a nano plugging agent is carried out according to Example 1, except that:
[0100] The amount of ammonium persulfate used was 0.12 g, the reaction temperature was 75° C., and the other steps and conditions were consistent with those in Example 1. The filtration loss at normal temperature and pressure was 21.2 mL.
[0101] Comparative Example 5
[0102] A method for preparing a nano plugging agent is carried out according to Example 1, except that:
[0103] The amount of ammonium persulfate used was 0.15 g, the reaction temperature was 85° C., and the other steps and conditions were consistent with those in Example 1. The filtration loss at normal temperature and pressure was 19.6 mL.
Claims
1. A method for preparing a nano zinc oxide plugging agent with a hard-inner-and-soft-outer core-shell structure for marine drilling fluid, comprising the following steps: The acrylamide aqueous solution, 2-acrylamide-2-methylpropanesulfonic acid solution and KH570 modified nano zinc oxide solution are uniformly mixed; under a protective atmosphere and stirring conditions, an initiator aqueous solution is added dropwise; the mixture is stirred and reacted under a protective atmosphere, and then washed, dried and crushed to obtain a modified nano zinc oxide core-shell structure plugging agent for marine drilling fluid.
2. The preparation method according to claim 1, characterized in that: The mass concentration of the acrylamide aqueous solution is 6-15%.
3. The preparation method according to claim 1, characterized in that: The mass concentration of the 2-acrylamide-2-methylpropanesulfonic acid solution is 20-26%, and the solvent is water.
4. The preparation method according to claim 1, characterized in that: The mass concentration of KH570 modified nano zinc oxide solution is 15-25%, and the solvent is water.
5. The preparation method according to claim 1, characterized in that: The molar ratio of acrylamide to 2-acrylamido-2-methylpropanesulfonic acid is (1-3):
1.
6. The preparation method according to claim 1, characterized in that: The molar ratio of acrylamide to KH570 modified nano zinc oxide is 1:(1-6).
7. The preparation method according to claim 1, characterized in that: The mixing is carried out under stirring conditions, with a stirring rate of 200-300 rpm, a stirring time of 10-20 minutes, and a mixing temperature of 15-25° C.; the protective atmosphere is nitrogen.
8. The preparation method according to claim 1, characterized in that: The mass concentration of the initiator aqueous solution is 0.9%-1.5%; the initiator is ammonium persulfate, the mass of the initiator is 0.5%-1% of the total mass of acrylamide, dimethyldiallyl ammonium chloride and KH570 nano zinc oxide, the dropping rate of the initiator aqueous solution is one drop every 2-4 seconds, after the initiator is added, the stirring reaction temperature is 65-85°C, the stirring speed is 20-35rpm, the stirring reaction time is 6h, washing is performed using ethanol; the drying temperature is 65-85°C.
9. A nano zinc oxide plugging agent with a hard-inside and soft-outside core-shell structure for marine drilling fluid, prepared by the method according to any one of claims 1 to 8.
10. The use of the inner-rigid and outer-flexible core-shell structured nano zinc oxide plugging agent for marine drilling fluid as claimed in claim 9 is used as a plugging agent in deep-water reservoir drilling to plug the micro-nano pores in the formation and inhibit the formation of natural gas hydrates, and the addition amount is 1-5g / 300-600mL.
Citation Information
Patent Citations
Salt-responsive high-temperature-resistant zwitterionic polymer filtrate reducer and preparation method and application thereof
CN112011318A
Synthesis of self-adaptive soft-outside and rigid-inside nano blocking agent and water-based drilling fluid
CN113355073A
Nano-silica graft polymer, preparation method and application thereof, and filtrate reducer
CN114163587A
Hydrophobic association high-performance water-based drilling fluid for shale formation as well as preparation method and application of hydrophobic association high-performance water-based drilling fluid
CN116396731A
Modified nano-zinc oxide plugging agent and oil-based drilling fluid
CN119119977A